Impact of work design and work-family conflict on professional gratification and life satisfaction. Insight from Nyamasheke District (International Journal of Scientific Research and Management (IJSRM), 2024)
Work-Family Conflict (WFC) is a prevalent challenge in modern workplaces, significantly impacting employee well-being. This study explores WFC dynamics and their effects on professional gratification and life satisfaction among Nyamasheke, Rwanda, employees. Investigating the interplay of work and family stressors, the study finds WFC insignificantly influences job and life satisfaction. The model used to understand the relationship between job and life satisfaction lacks efficacy, emphasizing the need for further context-specific exploration. Implications highlight the necessity for future studies to delve into unexplored facets of WFC, especially its connection with self-efficacy. The findings advocate for targeted employer policies addressing WFC challenges. The study recommends expanding research to diverse Nyamasheke groups for a comprehensive understanding of work-family dynamics. This pursuit of knowledge informs interventions and policies to enhance employee well-being amid the pervasive challenges of work-family conflict.